2018
DOI: 10.1016/j.ptsp.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of the shoulder of swimmers after a maximal effort test

Abstract: A maximal 3-min effort test resulted in altered scapular biomechanics. More studies are needed to verify if the changes correspond to a risk factor for injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…The direct effect of IT on the BM results in a decrease in its contraction ability, stabilizing the elbow joint during the catch stage in freestyle swimming stroke 71 73 . Additionally, the autonomous contraction ability of muscles is closely related to muscle electromyography (EMG) activity 22 , 74 77 . It remains unknown whether the IT-induced improvement in MVC for swimmers with EP also influences muscle EMG activity.…”
Section: Discussionmentioning
confidence: 99%
“…The direct effect of IT on the BM results in a decrease in its contraction ability, stabilizing the elbow joint during the catch stage in freestyle swimming stroke 71 73 . Additionally, the autonomous contraction ability of muscles is closely related to muscle electromyography (EMG) activity 22 , 74 77 . It remains unknown whether the IT-induced improvement in MVC for swimmers with EP also influences muscle EMG activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the adaptive changes in strength of the periscapular muscles in swimmers after swim training, which may be associated with SD and altered neuromuscular control. There were more competitive swimmers exhibiting SD due to muscle fatigue after swim training than before training 25 , 26 Swimmers also demonstrate a decrease in SA activity and an increase in internal rotation and anterior tilting of the scapula during scaption after maximal-effort stroke exercise 27 The possible reason was SA fatigue since SA alternately played as a scapular stabilizer and protractor throughout the swimming stroke. However, more internal rotation and anterior tilting of the scapula with higher activity of the SA during scaption were noticed in swimmers than in nonpractitioners 12 The increases in SA activity didn’t favor tilting the scapula posteriorly and rotating it externally may be due to insufficient strength.…”
Section: Discussionmentioning
confidence: 99%
“…После трехминутного максимального усилия у пловцов кролем на груди меняется биомеханика лопаток: усиливается их внутренняя их ротация при всех положениях плеча и передний наклон лопатки при передней флексии плеча на 120º. Это может создавать риск травмы плеча [4].…”
Section: результаты и обсуждениеunclassified